An evaluation of the DRI‐ETG EIA method for the determination of ethyl glucuronide concentrations in clinical and post‐mortem urine. Issue 6 (28th February 2012) - Turfus, Sophie C.; Vo, Tu; Niehaus, Nadia; Gerostamoulos, Dimitri; Beyer, Jochen
<x xml:space="preserve">Abstract</x> A commercial enzyme immunoassay for the qualitative and semi‐quantitative measurement of ethyl glucuronide (EtG) in urine was evaluated. Post‐mortem (n=800), and clinical urine (n=200) samples were assayed using a Hitachi 902 analyzer. The determined concentrations were compared with those obtained using a previously published liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) method for the quantification of EtG and ethyl sulfate. Using a cut‐off of 0.5 µg/ml and LC‐MS/MS limit of reporting of 0.1 µg/ml, there was a sensitivity of 60.8% and a specificity of 100% for clinical samples. For post‐mortem samples, sensitivity and specificity were 82.4% and 97.1%, respectively. When reducing the cut‐off to 0.1 µg/ml, the sensitivity and specificity were 83.3% and 100% for clinical samples whereas for post‐mortem samples the sensitivity and specificity were 90.3 % and 88.3 %, respectively. The best trade‐offs between sensitivity and specificity for LC‐MS/MS limits of reporting of 0.5 and 0.1 µg/ml were achieved when using immunoassay cut‐offs of 0.3 and 0.092 µg/ml, respectively. There was good correlation between quantitative results obtained by both methods but analysis of samples by LC‐MS/MS gave higher concentrations than by enzyme immunoassay (EIA), with a statistically significant proportional bias (P<0.0001, Deming regression) for both sample types. The immunoassay is reliable for the qualitative and semi‐quantitative presumptive detection of ethyl glucuronide in urine. Copyright © 2012 John Wiley & Sons, Ltd.